Capitalismo, ciencias sociales y colonialidad - Sanchez-Antonio, Juan Carlos (Comparative Cultural Studies: European and Latin American Perspectives, 2022)
I pretend to analyze the relationships between capitalism, coloniality and social sciences from the Latinamerican decolonial perspective. From the outset I defend the thesis that the brutal use of blacks and blacks, Indians and Indians, in the extraction of an invaluable amount of gold and silver in America, served as a historical condition for the globalization of capital and the industrialization of Europe, creating historical colonial conditions on which the social sciences will build their scientific discourse against the light. I briefly examine the way in which the Euro-Northamerican social sciences have served as a colonial knowledge-power device for the sub-alternation of non-scientific knowledge. In the end, I pondered the importance of overcoming modernity-postmodernity as the foundation of capital from a transmodern horizon that goes beyond capitalism.